Modelagem etnoecológica da percepção de vulnerabilidades, riscos e impactos socioambientais em comunidades quilombolas da Baía de Todos os Santos - Santos, Andréa Iridan dos (2013)
This research was conducted in the Quilombola communities of São Braz in Santo Amaro and in the Salamina Putumuju community of Maragogipe, both located in the state of Bahia, with the aim of developing ethno-ecological models that describe and reflect on how the quilombola populations of these communities perceive, assess and respond to the socio-environmental impacts, risks and vulnerabilities existing in the Bay of All Saints. To this end, we conducted 67 semi-structured interviews; field observations; focus groups and ethnocartography. We confirmed that the participating communities recognized the serious situation of vulnerabilities, involving a range of aspects, of which the most important are: lack of entitlement to their lands; occupation of the land around them and plans for new, high impact, businesses; uncertain access to basic rights; dependence on natural resources (under chronic and severe threat) to carry out their production activities; the weakening of local organization; little synergy of the forces set up between the communities and government institutions, with little influence on the processes that define policies applied to the region and the locality. In terms of risks and impacts, the main source of threats identified by the groups are of technological origin, which involve industries, factories, petroleum plants, property development tourism, the Pedra do Cavalo hydroelectric dam and power plant, and the Enseada do Paraguaçu Shipyard. There are also threats that originate from an absence or inefficiency of the public authorities, such as: the presence of refuse dumps near to bodies of water; the direct discharge of sewage into the mangrove ecosystem; and the lack of inspection to prevent deforestation and the use of fishing explosives. According to the interviewees, fishing resources suffer the most intense impacts, including: a reduced number of fish, molluscs and crustaceans; the pollution and contamination of the sea, rivers and mangroves; fish mortality; and the disappearance of fish and shellfish species. The community capacity to respond and adapt to the impacts and risk they face is small, their defence strategy is based on the construction of partnerships; reporting infringements to the Public Prosecutor’s Office and through the construction of production alternatives for income generation through agriculture and extractivism. It was found that these agro-fishing communities have a great proprietorial knowledge of the ecosystems in which they live, as well as of the changes taking place. We also identified elements regarding impacts and risks that other types of studies have not considered. This study thus reinforces the assertion that the participation of local agents is an essential factor in the planning and management of traditional territories and the risks therein.